Mechanisms of muscle repair after peripheral nerve injury by electrical stimulation combined with blood flow restriction training - Xiaolei Chu; Jiaojiao Sun; Jiajia Liang; Wenjie Liu; Zheng Xing; Qi Li; Qingwen Li (Sports Medicine and Health Science)
This review elucidates the impact of electrical stimulation (ES) and blood flow restriction (BFR) training on muscle function. ES induces a transformation in muscle fibers type by rearranging myosin heavy chain isoform patterns. Additionally, it influences muscle protein synthesis and degradation through specific signaling pathways such as protein kinase B/mechanistic target of rapamycin (Akt/mTOR), as well as via autophagy and the ubiquitin-proteasome system, thereby effectively maintaining muscle mass. BFR, on the other hand, restricts muscle blood flow, leading to metabolic products accumulation and localized hypoxia, which not only promotes the recruitment of fast-twitch fibers but also activates the mTOR signaling pathway, enhancing muscle protein synthesis. The combination of ES and BFR synergistically facilitates muscle protein synthesis through the mTOR pathway, thereby accelerating the recovery of muscle function following peripheral nerve injury.